Preparation And Characterization Of Cr/Activated Carbon Catalyst From Palm Empty Fruit Bunch - Zainal Fanani; Dedi Rohendi; Tri Kurnia Dewi; Muhammad Dzulfikar A (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2016)
Preparation and characterization of Cr/activated carbon catalyst from palm empty fruit bunch had been done. The research were to determine the effect of carbonization temperature towards adsorption of ammonia, iodine number, metilen blue number, and porosity of activated carbon and Cr/activated carbon catalyst. The determination of porosity include surface area, micropore volume and total pore volume. The results showed the best carbonization temperature activated carbon and Cr/activated carbon catalyst at 700°C. The adsorption ammonia of activated carbon and Cr/activated carbon catalyst as 6.379 mmol/g and 8.1624 mmol/g. The iodine number of activated carbon and Cr/activated carbon catalyst as 1520.16 mg/g and 1535.67 mg/g. The metilen blue number of activated carbon and Cr/activated carbon catalyst as 281.71 mg/g and 319.18 mg/g. The surface area of activated carbon and Cr/activated carbon catalyst as 1527.80 m2/g and 1652.58 m2/g. The micropore volume of activated carbon and Cr/activated carbon catalyst as 0.7460 cm3/g and 0.8670 cm3/g. The total pore volume of activated carbon and Cr/activated carbon catalyst as 0.8243 cm3/g and 0.8970 cm3/g.Keywords : activated carbon, palm empty fruit bunch, porosity, catalyst, chromium